Stabilization for a finite time in problems with free boundary for some classes of nonlinear second-order equations - Berezansky, Yu. M.; Mitropolskiy, Yu. A.; Shkhanukov-Lafishev, M. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain estimates for the time of stabilization of solutions of problems with free boundary for one-dimensional quasilinear parabolic equations.